Unexpected heterogeneity derived from Cas9 ribonucleoprotein‐introduced clonal cells at the HPRT1 locus. (9th February 2018) - Sakuma, Tetsushi; Mochida, Keiji; Nakade, Shota; Ezure, Toru; Minagawa, Sachi; Yamamoto, Takashi
Abstract : Single‐cell cloning is an essential technique for establishing genome‐edited cell clones mediated by programmable nucleases such as CRISPR‐Cas9. However, residual genome‐editing activity after single‐cell cloning may cause heterogeneity in the clonal cells. Previous studies showed efficient mutagenesis and rapid degradation of CRISPR‐Cas9 components in cultured cells by introducing Cas9 ribonucleoproteins (RNPs). In this study, we investigated how the timing for single‐cell cloning of Cas9 RNP‐transfected cells affected the heterogeneity of the resultant clones. We carried out transfection of Cas9 RNPs targeting several loci in the HPRT1 gene in HCT116 cells, followed by single‐cell cloning at 24, 48, 72 hr and 1 week post‐transfection. After approximately 3 weeks of incubation, the clonal cells were collected and genotyped by high‐resolution microchip electrophoresis and Sanger sequencing. Unexpectedly, long‐term incubation before single‐cell cloning resulted in highly heterogeneous clones. We used a lipofection method for transfection, and the media containing transfectable RNPs were not removed before single‐cell cloning. Therefore, the active Cas9 RNPs were considered to be continuously incorporated into cells during the precloning incubation. Our findings provide a warning that lipofection of Cas9 RNPs may cause continuous introduction of gene mutations depending on the experimental procedures. Abstract : We investigated the appropriate timing of single‐cell cloning after the introduction of CRISPR‐Cas9 into cultured cells. Surprisingly, long‐term incubation after transfection caused highly heterogenous clones in our experiments. This unexpected heterogeneity was considered to depend on the protocol of transfection and incubation.